Developing sensor‐based irrigation scheduling that maximizes soybean grain yield, irrigation water use efficiency, and returns above irrigation costs. Issue 1 (22nd May 2020) - Wood, C. W.; Krutz, L. J.; Henry, W. B.; Irby, T.; Orlowski, J. M.; Bryant, C. J.; Atwill, R. L.; Spencer, G. D.; Mills, B. E.
Abstract: Agricultural withdrawal from the Mississippi River Valley Alluvial aquifer (MRVAA) exceeds its recharge rate, causing groundwater declines and cones of depression across the midsouthern United States. This research was conducted to determine whether sensor‐based irrigation scheduling of soybean [ Glycine max (L.) Merr.] could improve yield and profitability while minimizing consumptive water use. The effects of season‐long soil water potential (SWP) threshold (−50 and −85 centibar [cbar]) on consumptive water use and on agronomic and economic parameters were compared with scheduling irrigations as a function of growth stage (VN–R2, R3–R4, and R5–R6.5) and SWP threshold (−50, −85, and −125 cbar) on a Dundee silty clay loam (fine‐silty, mixed, active, thermic Typic Endoaqualfs) near Stoneville, MS, from 2015 through 2017. Decreasing the season‐long SWP threshold for soybean from −50 to −85 cbar reduced consumptive water use 49% while having no adverse effect on yield, returns above irrigation costs, or irrigation water use efficiency (IWUE). Adjusting the irrigation threshold as a function of growth stage did not improve yield or returns above irrigation costs. Our data indicate that maintaining a season‐long irrigation threshold of −85 cbars optimizes yield, returns above irrigation costs, and IWUE efficiency while reducing withdrawal for soybean irrigation from the MRVAA up to 49% relative to the −50 cbar producer standard.